KONSEP EDUPREUNEURSHIP DAN IMPLEMENTASINYA BAGI LULUSAN PERGURUAN TINGGI - Azizah, Azizah (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2025)
This study aims to determine the concept of edupreneurship and its implementation for college graduates. The research method is a qualitative research method. While the research approach is library research. Data collection techniques with documentation. Edupreneurship comes from the words education and entrepreneurship which mean education and entrepreneurship, so edupreneurship means entrepreneurship education, namely introducing entrepreneurial concepts to instill an entrepreneurial spirit, including being creative, innovative, daring to take risks and being highly competitive. That way, college graduates are able to compete in the industrial world. Therefore, edupreneurship is important to be taught in educational institutions and colleges in order to increase the competitiveness of college graduates after completing their education. Based on research conducted at Harvard University, two skills that support a person's success are 80% soft skills and 20% hard skills. Through edupreneurship, the skills possessed by students can be improved.